Effectiveness of a Self-monitoring Device for Urinary Sodium-to-Potassium Ratio on Dietary Improvement in Free-Living Adults: a Randomized Controlled Trial - Iwahori, Toshiyuki; Ueshima, Hirotsugu; Ohgami, Naoto; Yamashita, Hideyuki; Miyagawa, Naoko; Kondo, Keiko; Torii, Sayuki; Yoshita, Katsushi; Shiga, Toshikazu; Ohkubo, Takayoshi; Arima, Hisatomi; Miura, Katsuyuki (Journal of epidemiology, 2018)
Reducing the urinary sodium-to-potassium ratio is important for reducing both blood pressure and risk of cardiovascular disease. Among free-living Japanese individuals, we carried out a randomized trial to clarify the effect of lifestyle modification for lowering urinary sodium-to-potassium ratio using a self-monitoring device. This was an open, prospective, parallel randomized, controlled trial. Ninety-two individuals were recruited from Japanese volunteers. Participants were randomly allocated into intervention and control groups. A month-long dietary intervention on self-monitoring urinary sodium-to-potassium ratio was carried out using monitors (HEU-001F, OMRON Healthcare Co., Ltd., Kyoto, Japan). All participants had brief dietary education and received a leaflet as usual care. Monitors were handed out to the intervention group, but not to the control group. The intervention group was asked to measure at least one spot urine sodium-to-potassium ratio daily, and advised to lower their sodium-to-potassium ratio toward the target of less than 1. Outcomes included changes in 24-hour urinary sodium-to-potassium ratio, sodium excretion, potassium excretion, blood pressure, and body weight in both groups. Mean measurement frequency of monitoring was 2.8 times/day during the intervention. Changes in urinary sodium-to-potassium ratio were -0.55 in the intervention group and -0.06 in the control group (P = 0.088); respective sodium excretion changes were -18.5 mmol/24 hours and -8.7 mmol/24 hours (P = 0.528); and corresponding potassium excretion was 2.6 mmol/24 hours and -1.5 mmol/24 hours (P = 0.300). No significant reductions were observed in either blood pressure or body weight after the intervention. Providing the device to self-monitor a sodium-to-potassium ratio did not achieve the targeted reduction of the ratio in "pure self-management" settings, indicating further needs to study an effective method to enhance the synergetic effect of dietary programs and self-monitoring practice to achieve the reduction. However, we cannot deny the possibility of reducing sodium-to-potassium ratio using a self-monitoring device.